Psychometric properties of the Nepali language version of the Depression Anxiety Stress Scales (DASS‐21) - Deependra Kaji Thapa; Denis Visentin; Rachel Kornhaber; Michelle Cleary (Wiley, 2022)
Abstract Aim To assess the psychometric properties of the Nepali language version of the Depression Anxiety Stress Scales (DASS‐21). Design Descriptive, cross‐sectional survey. Methods The DASS‐21 was administered (May-July 2019) among 794 randomly selected older adults aged ≥60 years. Factor structure was evaluated using exploratory and confirmatory factor analyses. Cronbach's alpha was calculated, and correlation analyses with quality of life evaluated convergent validity. Results Exploratory factor analysis indicated that the 21 items loaded on three factors, with factor loadings ranging from 0.50-0.88. Confirmatory factor analysis suggested a four‐factor model including the three subscales and an additional common 'general distress' factor, which demonstrated a better overall fit. Good reliability was found for each subscale, with Cronbach's alphas 0.79 for Anxiety, 0.91 for Stress, and 0.93 for Depression. The Nepali language version of the DASS‐21 satisfied convergent validity with all subscales depicting significant negative correlations with quality of life demonstrating adequate psychometric properties.